QUALITY ASSURANCE IN VOCATIONAL AND TECHNICAL EDUCATION TEACHER TRAINING PROGRAMME FOR SUSTAINABLE TECHNOLOGICAL DEVELOPMENT IN NIGERIA - Saba, Tswanya Moses; Ibrahim, Dauda; Kareem, Wahab (Sokoto Educational Review, 2011)
It is acknowledged that no educational system can rise better than the quality of teachers who run and operate it and more importantly, the importance of Vocational and Technical Education (VTE) to national development are more reasons why those who are charged to deliver it must not fail. The extent to which a teacher is able to bring about all expectations is dependent on the quality of training she received during the training and this calls for quality assurance in VTE teachers training programmes. Some of the issues considered in this write up include among others; why quality assurance in VTE teachers training programmes, how to actualize quality assurance in VTE teachers training programmes and implications of quality in VTE teachers training programmes. To achieve this, the following recommendations were made among others includes; VTE teachers training programmes should adequately expose students on industrial practices, Facilities should be provided for VTE teacher training programmes to enable them to acquire relevant skills to be passed to students after graduation and teachers in training should be properly trained on entrepreneurial skills to enable them to pass it to others.